KONDISI SOSIAL PETANI KOPI DESA UJUNG BULU, KECAMATAN RUMBIA, KABUPATEN JENEPONTO - Sutrisno Sutrisno (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
Abstract This study aims to determine the socio-economic conditions of Ujung Bulu Village, Rumbia District, Jeneponto Regency. This research uses descriptive quantitative research methods which are generally economic conditions viewed from economic aspects such as livelihoods, welfare and income levels. then from the social aspect seen from the level of education, health and perceptions of young people. The data source used 187 household respondents. Data were collected using a questionnaire and supported by structured interviews.The results showed that the level of income of the majority of people in Ujung Bulu Village was middle to lower, as well as the income of the agricultural sector community. The majority of Ujung Bulu Village residents work as farmers, while other sectors are mostly traders.The majority of households in Ujung Bulu Village already have a decent place to live according to some criteria and ownership status of their own building. Based on the educational background in general, Ujung Bulu Village people have a low education level with the last level of education being the elementary school level. Keywords: Socio-Economic Conditions, Farming, Income, Education Level, Welfare